PENGARUH PEMAHAMAN STANDAR AKUNTANSI PEMERINTAH (SAP), SISTEM AKUNTANSI KEUANGAN DAERAH DAN PENGALAMAM PENGELOLAAN BARANG MILIK DAERAH TERHADAP KUALTAS LAPORAN KEUANGAN: (Studi Empiris Pada Pemerintah Provinsi Maluku) - HULISELAN, MENY (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2022)
The purpose of the study is to find out empirically the effect of understanding government accounting standards, regional financial accounting systems, experience in managing regional property on the quality of regional financial reports. This research is stand as empirical research by used purposive samping as sampling technique. The survey method was used in data collection and hypothesis testing through t-statistical test with a significance level of 0.05. The results of the study prove that the understanding of government accounting standards has a significant positive effect on the quality of financial statements, the regional financial accounting system has a significant positive effect on the quality of financial reports, but the experience of managing regional property has no significant effect on the quality of the financial statements of the Maluku Provincial Government.